Meritocratic economic policies in the service of the middle class - György, László; Horváth, Gergely; Molnár, Dániel (Public Finance Quarterly, 2024)
By the 2010s, the middle classes of the Western world had become the biggest losers from the accelerating globalisation processes since the 1970s. Several proposals have been made regarding what economic policies should be put in place to strengthen the lower classes. These would typically redistribute income from the rich to the poor. Hungary has chosen a particular path in response to the disadvantages of globalisation: in our interpretation, it has shifted income from the rent-seekers to the middle class. Based on our definition of the middle class, which takes into account income, wealth, housing and the need for intellectual and cultural development, the middle class in Hungary expanded from 34.9 to 54.6 percent of society between 2011 and 2021 – in ten years, it expanded one and a half times. In our research, we investigated which measures have contributed to this and whether this could be the basis of a meritocratic economic policy mix that could be used in other countries.